ANALISIS EFISIENSI BIAYA BAHAN BAKU, BIAYA TENAGA KERJA LANGSUNG DAN BIAYA OVERHEAD PABRIK TERHADAP RASIO PROFIT MARGIN PADA MIE AYAM BAKSO CAK NO SOLO - Aisyah, Nia; Handayani, Putri; Astaivada, Tia; Adiyanto, Mochammad Reza (Transpublika Publisher, 2023)
This study aims to analyze the efficiency of raw material costs, direct labor costs and factory overhead costs on the profit margin ratio at Bakso Cak No Solo Chicken Noodle. By doing cost efficiency, it can increase maximum profit. The study used a qualitative approach and descriptive data analysis techniques. Analysis of production cost efficiency uses a comparison between actual production costs and budget production costs. In this study using data from observation, interviews and documentation. From this study obtained the results that the efficiency of production costs on raw materials at the meatball chicken noodle shop is inefficient with a percentage of 125%, this shows that there is a difference between the actual production costs of raw materials. Thus, causing the Cak No Solo Meatball Chicken Noodle shop to experience a loss of Rp. 500,000. After making the efficiency of raw material costs, it was found that the actual raw material costs decreased by IDR 505,000, because of this the production costs became efficient with a percentage of 99%. With the efficiency of production costs, the profit earned by business actors increased by 0.94%, namely IDR 505,000. The NPM result of 81.03% is also obtained, which means that business actors are more efficient in managing costs and generating maximum profits from sales. The higher the NPM value means that the finances in the business are healthier and better.